2007
DOI: 10.1021/ja073094m
|View full text |Cite
|
Sign up to set email alerts
|

Immunomagnetic Diffractometry for Detection of Diagnostic Serum Markers

Abstract: Abstract:We describe an integrated approach for detection of diagnostic markers using in situ assembled optical diffraction gratings in combination with immunomagnetic capture. Folate receptor (FR), a serum protein indicative of various cancers, was chosen as a model system to demonstrate the potential of the method. Magnetic beads coupled to FR antibody were used to capture FR from serum. The FR-bound magnetic beads self-assembled onto microcontact-printed folate-coupled BSA (F-BSA) patterns to form diffracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 38 publications
(57 reference statements)
1
47
0
Order By: Relevance
“…It is known that immunomagnetic diffractometry for the detection of various important biomolecules related to diseases has shown potential as a simple and sensitive method [22,25]. In this paper, we demonstrated that the magnetic accumulation-based signal amplification method can be easily integrated with the existing immunomagnetic diffractometry methods.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…It is known that immunomagnetic diffractometry for the detection of various important biomolecules related to diseases has shown potential as a simple and sensitive method [22,25]. In this paper, we demonstrated that the magnetic accumulation-based signal amplification method can be easily integrated with the existing immunomagnetic diffractometry methods.…”
Section: Discussionmentioning
confidence: 87%
“…After reviewing the literature [22], the incubation times and concentrations related to PDMS stamping were optimized by trial and error. The PDMS stamp that contains 20 µm alternating lines was washed using an ultrasonic cleaner using 70% ethanol and rinsed using 70% ethanol followed by deionized (DI) water.…”
Section: Immobilization Of Bbsa On Gold Chipsmentioning
confidence: 99%
“…Biosensors based on micro-contact printed probes and immunomagnetic beads were used to detect biologically significant target molecules such as cancer related folate receptor [9], and platelet-derived growth factor (PDGF) [8], and cardiovascular disease related s-adenosyl homocusteine [7]. In these biosensing applications the number of beads on the surface is proportional to the target concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The printed lines are for sensing and the spacing between printed lines can be used for control, the alternating pattern enables diffraction measurements [8,9]. Different methods such as atomic force microscopy (AFM) [4], fluorescence microscopy [3], and X-ray photoelectron spectroscopy (XPS) [10] are used to quantify the binding of biomolecules on micro-contact printed lines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation